International business and trade - Martin, Matt (Intramuros, Manila, Philippines : Unlimited Books Library Services and Publishing Inc., 2021)
This book will show you how to survive and thrive in the borderless multicultural world. You can in turn pass on this information to your family and organization with such cultural awareness, beliefs and behaviours hat will be necessary for them to adopt to the global marketplace.
CHAPTER 1. Changing of profile of glo0bal business environment -- 2. Introduction to international trade -- 3. Rules on the regional economic integration -- 4. Rules governing import & export of goods -- Working in different parts of the world -- References.
Includes index.
Keywords: INTERNATIONAL TRADE